Analisis Pengaruh Infrastruktur, Investasi, Dan Tenaga Kerja Terhadap Pertumbuhan Ekonomi Di Jawa Tengah - Rhamarsal Chalify, Marsal (2021)
This research is a form of quantitative research that aims to determine the effect of infrastructure, investment and labor on the rate of economic growth in Central Java Province. This study uses data from 35 districts/cities in Central Java Province for the 2016-2019 period. The method used in this study is a panel data regression model with the selected model is the Fixed Effect Model (FEM). The results of this study indicate that (1) infrastructure affects economic growth in Central Java Province (2) investment does not affect economic growth in Central Java Province (3) labor affects economic growth in Central Java Province